2000
DOI: 10.1046/j.1365-2885.2000.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A from a toxicological perspective

Abstract: Ochratoxin A (OTA) is a widespread mycotoxin which is produced mainly by the mould fungi Aspergillus ochraceus and Penicillum verrucosum during the storage of cereals, cereal products and other plant-derived products such as herbs, spices, grapes, etc. By carry over from mouldy fodder, ochratoxin A is also found in pork meat, offal and sausages containing pork blood. When ingested as a food contaminant, OTA is very persistent in human beings with a blood half-life of 35 days after a single oral dosage due to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
174
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(181 citation statements)
references
References 51 publications
1
174
0
6
Order By: Relevance
“…Humans may take up OTA by consuming foods made from ochratoxincontaminated cereals and other products such as coffee, beer, wine and foods of animal origin (Kuiper-Goodman, 1991;Jorgensen et al, 1996;Petzinger and Ziegler, 2000). Studies surveying the OTA content of human blood samples have been performed in numerous countries of the world including Hungary, and such surveys have invariably detected a high rate of positivity (BreitholtzEmanuelsson et al, 1993;Kovács et al, 1995;Solti et al, 1997;Scott et al, 1998;Özcelik et al, 2001).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
See 2 more Smart Citations
“…Humans may take up OTA by consuming foods made from ochratoxincontaminated cereals and other products such as coffee, beer, wine and foods of animal origin (Kuiper-Goodman, 1991;Jorgensen et al, 1996;Petzinger and Ziegler, 2000). Studies surveying the OTA content of human blood samples have been performed in numerous countries of the world including Hungary, and such surveys have invariably detected a high rate of positivity (BreitholtzEmanuelsson et al, 1993;Kovács et al, 1995;Solti et al, 1997;Scott et al, 1998;Özcelik et al, 2001).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
“…In addition to the OTA contamination of human blood samples, the occurrence of ochratoxin in human colostrum has also been reported (Breitholtz-Emanuelsson et al, 1993;Kovács et al, 1995). The high rate of contamination found in blood samples was attributed to the common occurrence and unique k inetics of ochratoxin (Petzinger and Ziegler, 2000). StuderRohr et al (2000) found that orally administered OTA doses had a half-life of 840 hours in humans, which is much longer than the half-lives found in any other species.…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
See 1 more Smart Citation
“…Ochratoxin A is very widely detected in raw material and food products such as cereals, bread, coffee, dried wine fruits, as well as in beverages, for example beer, grape juice, and wine [1][2][3][4][5][6][7]. This toxin is produced by numerous fungal species belonging to the genera Aspergillus and Penicillium.…”
Section: Introductionmentioning
confidence: 99%
“…The kidney is the main target tissue of OTA toxicity [10,19]. In addition to its nephrotoxic effects, hepato-, terato-and immunotoxic activities of OTA have also been reported [18,24]. OTA has been classified as a putative human carcinogen by the International Agency for Research on Cancer (IARC [14]).…”
Section: Introductionmentioning
confidence: 99%